Pembuatan Selai Buah Naga Merah (Hylocereus polyrhizus) Dengan Variasi Penambahan Stevia - Evania, Maria Krisna; Ratiati, Ratiati; Deglas, Welly; Fransiska, Fransiska (Program Studi Teknologi Pangan, 2025)
Red dragon fruit (Hylocereus polyrhizus) is a leading horticultural commodity in West Kalimantan with high potential but limited shelf life, thus requiring product diversification such as jam processing. This study aimed to evaluate the effect of stevia addition on the chemical characteristics and quality of red dragon fruit jam. The main ingredient consisted of 200 g dragon fruit flesh processed with 50 g sugar, 3 g pectin, and 1 g citric acid under four treatments: control (without stevia), 0.5% stevia (V1), 0.75% stevia (V2), and 1% stevia (V3). Parameters observed included moisture content, total soluble solids, reducing sugar, and organoleptic properties. The results showed that moisture content ranged from 23.26–26.96%, with the lowest value obtained in V3 (23.26%). Total soluble solids were recorded between 23–24.6 °Brix, with V2 showing the highest value (24.6 °Brix). Reducing sugar decreased with increasing stevia concentration, from 13.53% (control) to 9.28% (V3). All treatments met the Indonesian National Standard (SNI) for jam, with a maximum allowable moisture content of 35%. The incorporation of stevia effectively reduced reducing sugar levels without significantly affecting total soluble solids, while producing a low-calorie jam potentially suitable for consumers with special dietary needs. Therefore, red dragon fruit jam sweetened with stevia can be considered a functional, value-added innovation that supports local food diversification and promotes healthy consumption trends.